Hubungan Support System Keluarga dengan Tingkat Kecemasan pada Anak Praseolah Akibat Hospitalisasi di RSU Imelda Pekerja Indonesia Medan - Ito, Mita Melinda (Journal of Nursing Update, 2019)
Hospitalization  in children is a process because  of a planning   or emergency reason  that  requires  the  child  to  stay  in  the  hospital   to  undergo   therapy  and treatment   until  returning   home.   During   the process,   the  child   can  experience psychological   changes  such  as feelings of fear,  sadness  and anxiety.  Based on the preliminary    survey  data   on  15  children   at  Imelda   Pekerja  Indonesia found   6 children experienced in mild anxiety, while  l 2 children experienced in severe anxiety while the support of good families was 4 people and less than 11 people.  The aim of this research  was to find  out the relationship  offamily support system  with the level of anxiety  in preschool  children due  to hospitalization  at Imelda Pekerja  Indonesia General Hospital Medan  Indonesia. The method used  in this study was an analytical survey with a cross sectional approach.   The populations in this study  were all children  who were  treated at the Imelda  Pekerja Indonesian   in 2018  were 32 people  while the samples   in this study were all  children  treated  amount 32 people at Imelda  Pekerja Indonesian   General Hospital  2018.  The technique  sampling  used in this  study  was  the  total sampling techniques  and the test was do~e by using chi-square test. Based  on the results  of statistical  tests at 95% confidence level  obtained p  =0.023  from  a = 0.05.   These results prove  that there  was a relationship  offamily support systems and the level of anxiety in preschool  children due to hospitalization. The  conclusion  in  this study  shows  that there  is a relationship   of family support system with the level of anxiety  in preschool  children  due to hospitalization. It is suggested to the health  workers to always provide  information and counseling to families  about family support  systems and child anxiety.